2007
DOI: 10.2193/2006.101
|View full text |Cite
|
Sign up to set email alerts
|

Population Irruptions of Northern Bobwhite: Testing an Age‐Specific Reproduction Hypothesis

Abstract: Age-specific reproduction has been suggested for northern bobwhite (Colinus virginianus) and has been hypothesized as a factor contributing to population irruptions. However, little research has been conducted on the subject. We conducted a laboratory and field study to determine if age-specific reproduction occurred in northern bobwhites. Our objectives were to compare 7 reproductive measures (% F nesting, date of first incubated nest, egg-laying rate, nesting rate, clutch size, egg mass, and egg hatchability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Apparent nest success overestimates nest survival (Mayfield 1961, Johnson 1979), but apparent nest success is less biased in Northern Bobwhite studies because most nests are found at a similar stage of incubation . Apparent nest success (47.6%, 10 of 21 nests successful) was within the range of published estimates (rangewide average 5 0.42, range 0.25-0.63; Sandercock et al 2008) and was similar to reported median values from Texas (49%; Hernandez et al 2007), Oklahoma (48%; Cox et al 2005), and Florida (45%; DeVos and Mueller 1993).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Apparent nest success overestimates nest survival (Mayfield 1961, Johnson 1979), but apparent nest success is less biased in Northern Bobwhite studies because most nests are found at a similar stage of incubation . Apparent nest success (47.6%, 10 of 21 nests successful) was within the range of published estimates (rangewide average 5 0.42, range 0.25-0.63; Sandercock et al 2008) and was similar to reported median values from Texas (49%; Hernandez et al 2007), Oklahoma (48%; Cox et al 2005), and Florida (45%; DeVos and Mueller 1993).…”
Section: Discussionsupporting
confidence: 86%
“…Study Site.-This study was conducted in a 125-km 2 area without fixed study area boundaries in west-central Cumberland County, New Jersey, USA (39u 229 N, 75u 159 W; hereafter the ''focal area'') during the Northern Bobwhite breeding season (1 May-30 Sep 2006-2007. Cumberland County is within the Outer Coastal Plain physiographic region, bordering Delaware Bay.…”
Section: Methodsmentioning
confidence: 99%
“…Estimates of nest success were comparable (in 2013) or higher (in 2014) to those reported in Texas (49%) [ 65 ], New Jersey (45.4%) [ 66 ]; Florida (41%) [ 67 ], and Kentucky (31.7%) [ 68 ]. Average clutch size on Felsenthal NWR was higher than the assumed range-wide average of 12 eggs [ 1 ]; and, with the exception of the hatchability rate in 2013; (77%), the pooled hatchability rate (86%) was in range compared to rates reported in the literature (80% - 96%) [ 20 ].…”
Section: Discussionsupporting
confidence: 50%
“…Consequently, 95% confidence intervals tended to be wide for study sites with relatively low number of detections. Bobwhite populations on southwestern rangelands are strongly influenced by weather and density fluctuates drastically (Hernández et al 2005, 2007). Thus, survey effort required to reach a sufficient number of detections or a target level of precision may be considerable during population lows.…”
Section: Discussionmentioning
confidence: 99%